Early Detection Of Non-Communicable Diseases (Ncds) On The Health Status Of Periodontal Tissue And Treatment Needs In The Elderly Group In Padangsari Banyumanik Village, Semarang City - Sariyem, Sariyem; Sadimin, Sadimin; Subekti, Ani; Sunardjo, Lanny (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Dental and oral disease is a disease that affects all age groups, both in children and adults, including the elderly. One of the health problems in the elderly is dental caries and periodontal disease. Dental and oral disease is a problem in Indonesia based on the 2004 Household Health Survey (SKRT), the prevalence rate of dental caries in Indonesia reached 90.05%. In a study, it was stated that periodontal disease can increase the risk of stroke by more than 50% at the age of 25-54 years, this is because bacteria in periodontal disease enter the blood vessels and follow the flow of capillaries to the brain. Other studies show that 95% of people over 65 years old have periodontal disease, and 70% of elderly people need periodontal care [1]. Efforts are made to overcome the problem of dental and oral diseases in the elderly by approaching health workers and dentists about the importance of dental and oral health. This can also be done by the formation of dental and oral health cadres who play a role in monitoring the dental health of the elderly in the activities of the elderly Posyandu [2]. Padangsari Village, Banyumanik District has an Elderly Posyandu which every month routinely carries out Elderly Posyandu activities with activities including routine general health checks, including blood pressure checks, uric acid checks, blood sugar checks, but for dental health, especially periondontal tissue, routinely has not been carried out. Dental examinations need to be done regularly in the elderly because one of the symptoms that arise in degenerative diseases can be monitored through the oral cavity. The general purpose of this study is to detect diseases that can manifest through the oral cavity through examinations, education in improving dental health maintenance and providing care needs to the elderly group in Padangsari Banyumanik Village, Semarang City. The results showed that, based on the Wilcoxon Signed Ranks Test on calculus scores before and after treatment in the elderly (N = 60), the values of Z = –6,751 and p = 0.000 (p < 0.05) were obtained. These results show that there is a very significant difference between the score before and after treatment. All respondents experienced a decrease in calculus scores after treatment, which indicated a positive effect of the intervention given.